Impact-resistant synergistic organic glass and manufacturing method thereof
By introducing nano-sized core-shell rubber particles into the plexiglass and forming chemical bonding and compatible interfaces, the problem of insufficient impact resistance of plexiglass in the prior art is solved, and efficient impact resistance is achieved, while maintaining the basic mechanical properties and high light transmittance of the material.
Patent Information
- Application Number
- CN202411979845.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-03-28
AI Technical Summary
While improving impact resistance, existing plexiglass is difficult to maintain the original basic mechanical properties and high visible light transmittance, and tougheners will affect the glass transition temperature and refractive properties of the material.
By introducing nano-sized core-shell rubber particles into the plexiglass, chemical bonding is formed between the core layer and the shell layer of the core layer of the core layer and the shell layer, and a compatible interface formed between the shell layer and the substrate is formed by polymerization and curing by the MMA permeability layer, the impact resistance of the material is enhanced.
While maintaining the basic mechanical properties and high visible light transmittance of the original plexiglass material, it can significantly improve its impact resistance, avoiding the negative impact of toughening agent on the material's thermomechanical behavior and refractive properties.
Smart Images

Figure CN119708383A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of organic glass, and in particular to an impact-resistant and enhanced organic glass and a method for manufacturing the same. Background Art
[0002] As a new type of polymer material with both strength and toughness, high-strength and toughness polymers have attracted extensive attention from academia and industry. In many key fields, such as rail transportation, aerospace, electronic communications and medical devices, the research progress of this material largely determines the development level of related cutting-edge technologies and people's living standards. In particular, transparent materials represented by plexiglass (Polymethyl methacrylate) have outstanding application advantages in the above fields, such as easy molding, good functional expansion and high light transmission, but the defects of low strength and insufficient toughness have caused a great degree of limitation to its large-scale promotion.
[0003] Studies have shown that adding a second phase, such as rubber particles, thermoplastic particles or mineral fillers, can improve the stiffness and impact resistance of the polymer matrix. However, due to changes in the microscopic composition structure, the toughening of the polymer matrix is usually accompanied by a decrease in the modulus, and the existing toughening agents will affect the glass transition temperature of the material, thereby affecting the thermomechanical behavior of the organic glass. In addition, the interface between the toughening agent particles and the organic glass is a two-phase transition zone, and their shrinkage separation and spatial migration cause the addition of an air layer, resulting in inconsistency in the refractive properties of the material, causing the organic glass to change from a transparent whole to a more spotted fog color, which will directly reduce the original stability of the organic glass during long-term use. The problems existing in the above-mentioned prior art need to be broken through urgently. Summary of the invention
[0004] In response to the above technical problems, the present application provides an impact-resistant enhanced organic glass and a method for manufacturing the same, which can improve the impact resistance of the organic glass while retaining the basic mechanical properties and high visible light transmittance of the original organic glass material.
[0005] In order to solve the above technical problems, the present application provides an impact-resistant synergistic organic glass, including a matrix and nano-sized core-shell particles dispersed in the matrix; in the transition region between the core layer and the shell layer of the core-shell particles, a chemical bond is formed between the first functional group contained in the core layer and the second functional group contained in the shell layer; the transition region between the shell layer and the matrix is a compatible interface formed by polymerization and curing of an MMA permeation layer, and in the transition region between the shell layer and the matrix, a chemical bond is formed between the second functional group contained in the shell layer and the third functional group contained in the matrix.
[0006] The present application also provides a method for manufacturing impact-resistant enhanced organic glass, comprising the following steps: S1, sequentially performing core layer seed formation, core layer growth, shell layer molding and impurity removal and concentration to obtain nano-sized core-shell particles, wherein a first functional monomer containing a first functional group is added during core layer growth; and a second functional monomer containing a second functional group is added during shell layer molding; S2, preparing a pre-dispersion liquid of the core-shell colloid particles, wherein the pre-dispersion liquid comprises the core-shell colloid particles, a dispersant and an MMA monomer; S3, preparing a liquid matrix material, wherein the liquid matrix material comprises a pre-dispersion liquid of the core-shell particles, a pre-polymerization liquid formed by bulk polymerization of MMA, a third functional monomer containing a third functional group, and a thermal initiator; S4, controlling the temperature conditions to polymerize the liquid matrix material to form a solid matrix, and at the same time, forming a chemical bond between the first functional group and the second functional group, and forming a chemical bond between the second functional group and the third functional group, to obtain impact-resistant enhanced organic glass.
[0007] In some embodiments, the step of performing core layer growth includes: forming a pre-emulsified solution consisting of a soft monomer, a surfactant, a cross-linking agent and the first functional monomer in a mass ratio of 100: (1 to 5): (1 to 5): (5 to 10); The solution is added dropwise to the core layer seed emulsion at a set rate until the addition is completed to obtain the core layer growth emulsion.
[0008] In some embodiments, the step of forming the shell layer includes: forming a pre-emulsified solution consisting of a hard monomer, a surfactant, a crosslinking agent and the second functional monomer in a mass ratio of 100: (1 to 5): (1 to 5): (5 to 10); The shell layer forming emulsion is obtained by dropping the emulsion into the core layer growth emulsion at a set rate until the dropping is completed.
[0009] In some embodiments, the core-shell particles have a particle size of less than 200 nm.
[0010] In some embodiments, in S2, the mass ratio of the core-shell particles, the dispersant and the MMA monomer is 100: (0.5 ~ 2): (5 ~ 10).
[0011] In some embodiments, in the liquid matrix material, the mass ratio of the prepolymer liquid, the pre-dispersion liquid of the core-shell particles and the third functional monomer is (60 ~ 90): (5 ~ 30): (5 ~ 10), and the mass proportion of the thermal initiator in the liquid matrix material is ≤0.8%.
[0012] In some embodiments, the viscosity of the prepolymer solution is 20 to 150 s at 25° C. when the coating is poured out of a 4-cup coating.
[0013] In some embodiments, the first functional group and the third functional group are epoxy groups, and the second functional group is carboxyl groups; or, the first functional group and the third functional group are hydroxyl groups, and the second functional group is carboxyl groups.
[0014] The present application also provides an impact-resistant enhanced organic glass, which is manufactured using the manufacturing method of the impact-resistant enhanced organic glass as described above.
[0015] The impact-resistant synergistic organic glass of the present application and its manufacturing method include: performing core layer seed formation, core layer growth, shell layer molding and impurity removal and concentration to obtain nano-sized core-shell colloid particles, adding a first functional monomer containing a first functional group when the core layer grows, and adding a second functional monomer containing a second functional group when the shell layer is molded; forming a pre-dispersion liquid including core-shell colloid particles, a dispersant and an MMA monomer; preparing a liquid matrix material; controlling the temperature conditions to polymerize the liquid matrix material to form a solid matrix, at which time the transition region between the shell layer and the matrix is a compatible interface formed by the polymerization and curing of the MMA permeation layer, so that a chemical bond is formed between the first functional group and the second functional group, and a chemical bond is formed between the second functional group and the third functional group, so as to obtain the impact-resistant synergistic organic glass. The present application can improve the impact resistance of organic glass while retaining the original basic mechanical properties and high visible light transmittance. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 It is a schematic diagram of the efficacy of an impact-resistant synergistic organic glass in an embodiment of the present application.
[0017] Figure 2 It is a schematic flow chart of a method for manufacturing an impact-resistant and enhanced organic glass in an embodiment of the present application.
[0018] Figure 3 It is a schematic diagram of the process principle of preparing core-shell colloid particles in the examples of the present application.
[0019] Figure 4 It is a schematic diagram of the process principle of a method for manufacturing impact-resistant enhanced organic glass in an embodiment of the present application.
[0020] Figure 5It is one of the results of transmission electron microscopy characterization of the pre-dispersion liquid of the core-shell colloid particles obtained in step S2 of Example 3 of the present application.
[0021] Figure 6 This is the second result of transmission electron microscopy characterization of the pre-dispersion of core-shell colloid particles obtained in step S2 of Example 3 of the present application.
[0022] Figure 7 This is the third result of transmission electron microscopy characterization of the pre-dispersion of core-shell colloid particles obtained in step S2 of Example 3 of the present application.
[0023] Figure 8 It is a comparison of UV-Vis spectra of Examples 1 to 3 and the control group in this application. DETAILED DESCRIPTION
[0024] The following is an explanation of the implementation of the present application by means of specific embodiments. People familiar with the art can easily understand other advantages and effects of the present application from the contents disclosed in this specification.
[0025] In the following description, reference is made to the accompanying drawings, which describe several embodiments of the present application. It should be understood that other embodiments may be used and that mechanical, structural, electrical, and operational changes may be made without departing from the spirit and scope of the present application. The following detailed description should not be considered limiting, and the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the present application.
[0026] Although the terms first, second, etc. are used herein to describe various elements in some instances, these elements should not be limited by these terms. These terms are only used to distinguish one element from another element.
[0027] Furthermore, as used in this article, the singular forms "one", "an" and "the" are intended to include plural forms as well, unless there is an indication to the contrary in the context. It should be further understood that the terms "comprise", "include" indicate the presence of the described features, steps, operations, elements, components, projects, kinds, and / or groups, but do not exclude the presence, occurrence or addition of one or more other features, steps, operations, elements, components, projects, kinds, and / or groups. The terms "or" and "and / or" used herein are interpreted as inclusive, or mean any one or any combination. Therefore, "A, B or C" or "A, B and / or C" means "any of the following: A; B; C; A and B; A and C; B and C; A, B and C". Exceptions to this definition will only occur when the combination of elements, functions, steps or operations is inherently mutually exclusive in some way.
[0028] First embodiment The present application provides an impact-resistant synergistic organic glass, which comprises a matrix and nano-sized core-shell colloid particles dispersed in the matrix.
[0029] The core-shell particles include a core layer and a shell layer covering the core layer. In some embodiments, the soft monomer forming the core layer is selected from at least one of butadiene and butyl acrylate, and the hard monomer forming the shell layer is selected from at least one of methyl methacrylate, styrene and acrylonitrile.
[0030] In the transition region between the core layer and the shell layer of the core-shell colloid, a chemical bond is formed between the first functional group contained in the core layer and the second functional group contained in the shell layer, thereby forming a robust connection between the core layer and the shell layer with excellent compatibility and reliable bonding strength.
[0031] The transition area between the shell layer and the matrix is a compatible interface formed by the polymerization and curing of the MMA permeation layer, and in the transition area between the shell layer and the matrix, a chemical bond is formed between the second functional group contained in the shell layer and the third functional group contained in the matrix. In this way, the transition area between the shell layer and the matrix of the core-shell colloid is an ultra-robust connection state formed by chemical bonding and the polymerization and curing of the MMA permeation layer, with more excellent compatibility and more reliable bonding strength, solving the problem of inconsistent refractive properties of materials caused by the shrinkage separation of the two-phase transition area and the increase of the air layer caused by spatial migration, that is, the problem of changing from a transparent whole to a more spotty fog color.
[0032] In some embodiments, the particle size of the core-shell particles is less than 200 nm, which is much lower than the starting point of the visible light range (380 nm).
[0033] The specific efficacy of the impact-resistant synergistic organic glass provided in the embodiments of the present application is expressed as follows: Figure 1 As shown. When the impact-resistant plexiglass encounters strong external stress impact, 1) due to the presence of core-shell particles, the matrix stress diffuses circumferentially along the core-shell particles, dispersing the absorption efficiency of the matrix per unit area for impact strength and increasing the impact toughness of the matrix; 2) due to the presence of core-shell particles, the diffusion of matrix cracks is blocked and passivated, and the development of small cracks into destructive through-cracks is stopped in time; 3) nano-scale core-shell particles show a large specific surface area, that is, the contact area is large enough, and when subjected to external forces, the connection sites or surfaces derived from the elastic deformation of the core-shell particles themselves are extremely abundant, which can dissipate more impact energy, further increase the failure threshold of the matrix, and protect the structural safety of the material.
[0034] The impact-resistant synergistic organic glass of the present application has a core-shell colloid particle size much smaller than the starting wavelength of the visible light range, and chemical bonds are formed between the core layer and the shell layer, and between the shell layer and the organic glass matrix, respectively, to further increase the interlayer compatibility and bonding strength of the two-phase material, and while the organic glass obtains better impact resistance, it hardly affects the light transmission performance of the organic glass. In addition, the interface between the core-shell colloid particle and the organic glass is a reliable connection superimposed by chemical bonding and compatible interface polymerization, which solves the problem of inconsistent refractive properties of the material caused by the shrinkage separation in the two-phase transition zone and the increase of the air layer caused by spatial migration, resulting in spotty fog. While improving the impact resistance of the organic glass, the basic mechanical properties and high visible light transmittance of the original organic glass material are also retained.
[0035] Second embodiment Figure 2 Schematic diagram of a method for manufacturing an impact-resistant plexiglass in an embodiment of the present application. Figure 2 As shown, the present application also provides a method for manufacturing impact-resistant enhanced organic glass, comprising the following steps: S1, sequentially performing core layer seed formation, core layer growth, shell layer molding and impurity removal and concentration to obtain nano-sized core-shell particles, wherein a first functional monomer containing a first functional group is added during core layer growth; and a second functional monomer containing a second functional group is added during shell layer molding; S2, preparing a pre-dispersion liquid of core-shell colloid particles, the pre-dispersion liquid comprising core-shell colloid particles, a dispersant and MMA monomer; S3, preparing a liquid matrix material, the liquid matrix material comprising a pre-dispersion liquid of core-shell particles, a pre-polymerization liquid formed by bulk polymerization of MMA, a third functional monomer containing a third functional group, and a thermal initiator; S4, controlling the temperature conditions to polymerize the liquid matrix material to form a solid matrix, and at the same time, forming a chemical bond between the first functional group and the second functional group, and forming a chemical bond between the second functional group and the third functional group, to obtain impact-resistant enhanced organic glass.
[0036] Among them, when preparing the pre-dispersion liquid of the core-shell colloid particles, MMA monomer is added, and an MMA permeation layer can be formed outside the shell layer, which is very conducive to the homogenization of the core-shell colloid particles in the liquid matrix material. While the liquid matrix material is polymerized to form a solid matrix, the transition zone between the shell layer and the matrix is formed by the polymerization and curing of the MMA permeation layer, which has excellent compatibility and reliable bonding strength, and solves the problem of inconsistent refractive properties of the material caused by the shrinkage separation and spatial migration of the two-phase transition region, resulting in the generation of spot fog. In addition, in the transition zone between the shell layer and the matrix, a chemical bond is formed between the second functional group contained in the shell layer and the third functional group contained in the matrix, further improving the binding force. At the same time, in the transition zone between the core layer and the shell layer of the core-shell colloid particles, a chemical bond is formed between the first functional group contained in the core layer and the second functional group contained in the shell layer, thereby forming a robust connection between the core layer and the shell layer, which has excellent compatibility and reliable bonding strength. Therefore, while improving the impact resistance of organic glass, the basic mechanical properties and high visible light transmittance of the original organic glass material can be retained.
[0037] In some embodiments, step S1 includes in sequence: S11, core layer seed formation; S12, core layer growth; S13, shell layer molding; S14, impurity removal and concentration.
[0038] In S11, a multi-necked flask of suitable volume is taken, nitrogen is continuously introduced, and the flask is immersed in a constant temperature oil bath environment of 80°C. A first solution consisting of a surfactant and deionized water in a mass ratio of (0.1 ~ 0.5):100 is added, stirring (500 rpm) and a condensing device are turned on, a second solution consisting of a soft monomer and a cross-linking agent in a mass ratio of 100:(1 ~ 5) is added, stirring is continued for 15 min, a third solution consisting of a water-soluble initiator and deionized water in a mass ratio of (1 ~ 3):100 is added, and an emulsion polymerization reaction is started, which is continued for 60 min, and a fourth solution having an initiator concentration of 1 / 2 of the third solution is added, and the reaction is continued for 30 min to obtain a core layer seed emulsion.
[0039] In some embodiments, performing S12, a step of growing a nuclear layer, comprises: forming a pre-emulsified solution consisting of a soft monomer, a surfactant, a cross-linking agent and a first functional monomer containing a first functional group in a mass ratio of 100: (1 to 5): (1 to 5): (5 to 10); The solution is added dropwise to the core layer seed emulsion at a set rate until the addition is completed to obtain the core layer growth emulsion.
[0040] Specifically, a pre-emulsified solution consisting of a soft monomer, a surfactant, a cross-linking agent, and a first functional monomer in a mass ratio of 100: (1 ~ 5): (1 ~ 5): (5 ~ 10) is formed, and the solution is added dropwise at a rate of 2 mL / min until the end, and an emulsion for continuous growth of the core layer is obtained. Figure 2 and Figure 3 After completing step S12, a core layer is formed, and the core layer contains a first functional group, such as an epoxy group.
[0041] In some embodiments, performing S13, the step of shell layer forming, comprises: forming a pre-emulsified solution consisting of a hard monomer, a surfactant, a cross-linking agent and a second functional monomer containing a second functional group in a mass ratio of 100: (1 to 5): (1 to 5): (5 to 10); The shell layer forming emulsion is obtained by dropping the emulsion into the core layer growth emulsion at a set rate until the dropping is completed.
[0042] Specifically, a fifth solution with an initiator concentration of 1 / 5 of the third solution is added to form a pre-emulsified solution composed of a hard monomer, a surfactant, a crosslinking agent and a second functional monomer in a mass ratio of 100: (1~5): (1~5): (5~10), and the solution is added dropwise at a rate of 5 mL / min until the end to obtain a shell forming emulsion. Figure 2 and Figure 3 After completing step S13, a shell layer is formed, and the shell layer contains a second functional group, such as a carboxyl group. Limited by the reaction temperature between the carboxyl group and the epoxy group, only a slight ring-opening reaction will occur below 100°C, and a small amount of chemical bonding will be formed between the two. Therefore, by the end of step S13, the first functional monomer in the core layer and the second functional monomer in the shell layer can undergo a relatively low degree of chemical reaction, which is specifically manifested in the formation of a small amount of chemical bonding between the epoxy group in the first functional monomer and the carboxyl group in the second functional monomer.
[0043] In step S14, the shell forming latex is filtered using a nylon filter with a mesh size of 2000 or higher, or a device with an interception aperture of less than 10 μm, to remove large particle impurities, to obtain a further purified latex, and to obtain a core-shell toughening agent composed of a large number of single core-shell particles under vacuum drying at 80°C overnight.
[0044] In some embodiments, the core-shell colloid particles prepared by the above method have a particle size of less than 200 nm.
[0045] In some embodiments, the surfactant used in step S1 is selected from sodium fatty acid R 1 COONa(R1=C 11 ~C17 )、Sodium dodecyl sulfate, sodium alkyl sulfonate R 2 SO3Na(R 2 =C 12 ~C 16 ), at least one of sodium alkyl aryl sulfonate.
[0046] A soft monomer selected from at least one of butadiene and butyl acrylate; a crosslinking agent selected from at least one of ethylene glycol dimethacrylate, N,N-dimethylacrylamide, pentaerythritol triacrylate, N, N'-methylenebisacrylamide, diallylamine, trimethylolpropane trimethacrylate, triethylene glycol dimethacrylate, 1,6-hexanediol diacrylate, trimethylolpropane triacrylate, diallyl terephthalate, diallyl isophthalate, diallyl phthalate, diallyl isocyanurate, triallyl isocyanurate, allyl methacrylate, triallyl cyanurate, ethylene glycol diacrylate, triethylene glycol diacrylate, diallylamine, 1,6-heptadiene-4-carboxylic acid, and 4-pentenoic anhydride; A water-soluble initiator selected from at least one of potassium persulfate, sodium persulfate, ammonium persulfate, calcium persulfate, and magnesium persulfate; The first functional monomer is an unsaturated monomer containing an epoxy group, selected from at least one of glycidyl methacrylate, allyl glycidyl ether, 4-hydroxybutyl acrylate glycidyl ether, and glycidyl acrylate; The second functional monomer is an unsaturated monomer containing a carboxyl group, selected from at least one of acrylic acid, methacrylic acid, myristic acid, 11-hexadecenoic acid, 10-undecenoic acid, 11-dodecenoic acid, isokaurenoic acid, 14-pentadecenoic acid, 22-tricosenoic acid, 12-tridecenoic acid, 11-dodecenoic acid, 4-aminohex-5-enoic acid, 9-methoxycarbonyldec-9-enoic acid, 3-butenoic acid, 2,2-dimethyl-3-butenoic acid, 2-methoxybutenoic acid, 2-methyl-3-butenoic acid, 4-pentenoic acid, cyclopentenoic acid, 3-pentenoic acid, 2-methyl-2-pentenoic acid, 4-amino-5-hexenoic acid, 5-hexenoic acid, 4-methyl-3-hexenoic acid, 6-heptenoic acid, 3-heptenoic acid, 2-heptenoic acid, 7-octenoic acid, 3-octenoic acid, 2-octenoic acid, and 8-nonenoic acid; The hard monomer is selected from at least one of methyl methacrylate, styrene and acrylonitrile.
[0047] In actual implementation, the first functional group and the second functional group are not limited to this. For example, they can also be hydroxyl and carboxyl, respectively. At a suitable temperature (such as 60 ~ 110 ° C), esterification reaction can occur to form a chemical bond. At this time, the compound where the first functional group is located and the compound where the second functional group is located also contain unsaturated bonds.
[0048] In some embodiments, in the process of preparing the core layer growth emulsion, the shell layer forming emulsion, and the liquid matrix material, a catalyst for accelerating the chemical bonding reaction between the first functional group and the second functional group and for accelerating the chemical bonding reaction between the second functional group and the third functional group can be added. Taking the first functional group and the third functional group as epoxy groups and the second functional group as carboxyl groups as an example, the catalyst includes at least one of triethylamine, diisopropylamine, N,N-dimethylbenzylamine, triphenylphosphine, chromium acetylacetonate, 3,5-diisopropyl chromium salicylate, 5-tert-butyl furancarboxylic acid chromium, and 5-isopropyl furancarboxylic acid chromium.
[0049] In some embodiments, in step S2, the mass ratio of the core-shell colloid particles, the dispersant and the MMA monomer is 100: (0.5 ~ 2): (5 ~ 10). Specifically, a mixed solution consisting of the core-shell colloid particles, the dispersant and the MMA monomer in a mass ratio of 100: (0.5 ~ 2): (5 ~ 10) is formed, and a non-invasive homogenizer with a revolution speed of 1000 rpm and a rotation speed of 500 rpm is used, respectively, and negative pressure mixing is performed for 10 minutes to obtain a pre-dispersion solution of the core-shell colloid particles.
[0050] Negative pressure refers to vacuuming to form an environment below one atmospheric pressure.
[0051] It is further explained that the use of MMA monomer as the pre-dispersion medium environment of the core-shell colloid particles in this step is very beneficial to the homogenization of the core-shell colloid particles in the liquid matrix material in the subsequent steps.
[0052] The dispersant used in step S2 is used to reduce the surface tension or surface energy of the core-shell toughening agent composed of a large number of single core-shell colloid particles, making it more conducive to forming a homogeneous pre-dispersion of the core-shell toughening agent in the medium environment of the MMA monomer. Specifically, the repulsive force generated by providing the same charge to the core-shell colloid particles through steric hindrance makes the large number of single core-shell colloid particles constituting the core-shell toughening agent stable and exist in a separated state. Other additives or reagents with different names but the same function can also be used as substitutes, such as substrate wetting agents, surface modifiers or leveling agents.
[0053] The dispersant can be selected from one or more of the following brands of reagents provided by BYK Chemicals of Germany, specifically BYK-300, BYK-301, BYK-302, BYK-306, BYK-307, BYK-308, BYK-310, BYK-320, BYK-322, BYK-323, BYK-326, BYK-331, BYK-330, BYK-332, BYK-333, BYK-336, BYK-341, BYK-342, BYK-344, BYK-345, BYK-346, BYK-347, BYK-348, BYK-349, BYK-350, BYK-352, BYK K-353, BYK-354, BYK-355, BYK-356, BYK-357, BYK-359, BYK-370, BYK-371, BYK-373, BYK-375, BYK-377, BYK-378, BYK-385, BYK-381, BYK-390, BYK- 394, BYK-399, BYK-392, BYK-110, BYK-190, BYK-W9010, BYK-P104S, BYK-2050, BYK-9076, BYK-163, BYK-168, BYK-170, BYK-192.
[0054] The dispersant can also be selected from one or more of the following brands of reagents provided by German Tego, specifically TEGO-610, TEGO-610S, TEGO-628, TEGO-630, TEGO-650, TEGO-651, TEGO-652, TEGO-653, TEGO-655, TEGO-656, TEGO-660C, TEGO-662C, TEGO-670, TEGO-671, TEGO-685, TEGO-688, TEGO-700, TEGO-710, TEGO-752W, TEGO- 240, TEGO-250, TEGO-260, TEGO-265, TEGO-270, TEGO-280, TEGO-500, TEGO-505, TEGO-510.
[0055] The dispersant can also be selected from one or more of the following brands of reagents provided by Hemmings Special Chemicals of Taiwan, China, specifically Levaslip 466, Levaslip 411, Levaslip 876, Levaslip 432, Levaslip 875, Levaslip 879, Levaslip 872, Levaslip 435, Levaslip 825, Levaslip 495, Levaslip835, and Levaslip 837.
[0056] In some embodiments, in step S3, in the liquid matrix material, the mass ratio of the prepolymer liquid, the pre-dispersion liquid of the core-shell particles, and the third functional monomer is (60-90): (5-30): (5-10), and the mass proportion of the thermal initiator in the liquid matrix material is ≤0.8%. In some embodiments, the viscosity of the prepolymer liquid is 20-150 s at 25°C for a 4-cup coating flow time.
[0057] In some embodiments, the third functional monomer may be a functional monomer that is the same as or different from the first functional monomer, and the third functional group may be a functional group that is the same as or different from the first functional group. For example, when the first functional group is an epoxy group and the second functional group is a carboxyl group, the third functional group may be an epoxy group. For another example, when the first functional group is a hydroxyl group and the second functional group is a carboxyl group, the third functional group may be a hydroxyl group. In this case, the compound where the first functional group is located, the compound where the second functional group is located, and the compound where the third functional group is located all contain unsaturated bonds.
[0058] The thermal initiator is an oil-soluble initiator, which functions to realize the polymerization reaction of the liquid matrix material under thermal initiation to form a solid matrix, and is selected from at least one of BPO, AIBN, and ABVN.
[0059] In one embodiment, the polymerization process forms a plate with a thickness of less than or equal to 10 mm, specifically, a water bath at 35 to 65°C for 2 to 12 hours, and a forced air bath at 105 to 135°C for 1 to 8 hours. When the thickness exceeds 10 mm, the specific water bath or air bath time should be adaptively extended according to actual conditions.
[0060] Further explanation: the temperature and time conditions in the above process can make the first functional monomer in the core layer and the second functional monomer in the shell layer fully react chemically, which is specifically manifested as a ring-opening reaction between the epoxy group in the first functional monomer and the carboxyl group in the second functional monomer to form a chemical bond; in addition, the second functional monomer in the shell layer and the third functional monomer in the matrix layer can also fully react chemically, which is specifically manifested as a ring-opening reaction between the carboxyl group in the second functional monomer and the epoxy group in the third functional monomer to form a chemical bond. The reaction process in the above two-phase interface region is detailed in Figure 4 .
[0061] The following are different embodiments for forming impact-resistant synergistic organic glass (the preparation process is shown in Figure 2 The process shown): Example 1 The steps include: S1. Preparation of core-shell colloid particles, including four stages: S11) core layer seed formation, S12) core layer growth, S13) shell layer molding, and S14) impurity removal and concentration. S11) Core layer seed formation, the specific process is: take a multi-mouth flask of suitable volume, continuously pass nitrogen, immerse in 80 ℃ constant temperature oil bath environment, add a first solution composed of a surfactant and deionized water with a mass ratio of (0.1 ~ 0.5): 100, start stirring (500 rpm) and condensing device, add a second solution composed of a soft monomer and a crosslinker with a mass ratio of 100: (0.1 ~ 0.5), continue stirring for 15 min, add a third solution composed of a water-soluble initiator and deionized water with a mass ratio of (1 ~ 3): 100, start emulsion polymerization, continue for 60 min, add a fourth solution with an initiator concentration of 1 / 2 of the third solution, continue for 30 min, and obtain a core layer seed emulsion. In this embodiment, the amount of surfactant and deionized water is 0.1 g and 100 g. The amount of soft monomer and crosslinker is 10 g and 0.01 g. The amounts of water-soluble initiator and deionized water used were 0.2 g and 20 g.
[0062] S12) The core layer continues to grow, and the specific process is: forming a pre-emulsified solution composed of a soft monomer, a surfactant, a cross-linking agent and a first functional monomer in a mass fraction ratio of 100: (1 ~ 5): (1 ~ 5): (5 ~ 10), and adding dropwise at a rate of 2 mL / min until the end, to obtain an emulsion in which the core layer continues to grow. In this embodiment, the amounts of the soft monomer, the surfactant, the cross-linking agent and the first functional monomer are 100 g, 1 g, 1 g and 5 g, respectively.
[0063] S13) Shell layer forming stage, the specific process is: add a fifth solution with an initiator concentration of 1 / 5 of the third solution to form a pre-emulsified solution composed of a hard monomer, a surfactant, a cross-linking agent and a second functional monomer in a mass ratio of 100: (1-5): (1-5): (5-10), and add dropwise at a rate of 5 mL / min until the end to obtain a shell layer forming emulsion. In this embodiment, the amounts of the hard monomer, the surfactant, the cross-linking agent and the second functional monomer are 100 g, 1 g, 1 g and 5 g, respectively.
[0064] S14) impurity removal and concentration process, specifically, filtering the obtained shell forming emulsion with a nylon filter of 2000 mesh or higher, or a device with an interception aperture of less than 10 μm to remove large particles of impurities, obtaining a further purified emulsion, and vacuum drying at 80° C. overnight to obtain core-shell particles composed of a large number of single core-shell particles.
[0065] S2. A pre-dispersion liquid of core-shell colloid particles is provided, and the specific process is: forming a mixed liquid consisting of core-shell colloid particles, a dispersant and an MMA monomer in a mass fraction ratio of 100: (0.5 ~ 2): (5 ~ 10), using a non-intrusive homogenizer with a revolution speed of 1000 rpm and a rotation speed of 500 rpm, respectively, and mixing under negative pressure for 10 minutes to obtain a pre-dispersion liquid of core-shell colloid particles. In this embodiment, the mass fractions of the core-shell colloid particles, the dispersant and the MMA monomer are 100, 0.5 and 5, respectively.
[0066] S3. Providing a liquid matrix material, wherein the liquid matrix material comprises a prepolymerized liquid formed by bulk polymerization of MMA, a pre-dispersed liquid of core-shell particles, a third functional monomer, and an oil-soluble initiator.
[0067] S4. Performing a polymerization reaction to form the liquid matrix material into a solid matrix.
[0068] Optionally, in step S1, The surfactant is selected from sodium fatty acid R 1 COONa(R1=C 11 ~C 17 )、Sodium dodecyl sulfate, sodium alkyl sulfonate R 2 SO3Na(R 2 =C 12 ~C 16 ), sodium alkyl aryl sulfonate (such as sodium dibutyl naphthalene sulfonate, rosin soap) at least one. In this embodiment, sodium dodecyl sulfate is specifically selected.
[0069] The soft monomer is selected from at least one of butadiene and butyl acrylate. In this embodiment, butyl acrylate is specifically selected.
[0070] The cross-linking agent is selected from at least one of ethylene glycol dimethacrylate, N,N-dimethylacrylamide, pentaerythritol triacrylate, N, N'-methylenebisacrylamide, diallylamine, trimethylolpropane trimethacrylate, triethylene glycol dimethacrylate, 1,6-hexanediol diacrylate, trimethylolpropane triacrylate, diallyl terephthalate, diallyl isophthalate, diallyl phthalate, diallyl isocyanurate, triallyl isocyanurate, allyl methacrylate, triallyl cyanurate, ethylene glycol diacrylate, triethylene glycol diacrylate, diallylamine, 1,6-heptadiene-4-carboxylic acid, and 4-pentenoic anhydride. In this embodiment, ethylene glycol dimethacrylate is specifically selected.
[0071] The water-soluble initiator is at least one selected from potassium persulfate, sodium persulfate, ammonium persulfate, calcium persulfate, and magnesium persulfate. Potassium persulfate is specifically selected in this embodiment.
[0072] The first functional monomer is an unsaturated monomer containing an epoxy group, and is selected from at least one of glycidyl methacrylate, allyl glycidyl ether, 4-hydroxybutyl acrylate glycidyl ether, and glycidyl acrylate. In this embodiment, glycidyl methacrylate is specifically selected.
[0073] The second functional monomer is an unsaturated monomer containing a carboxyl group, selected from at least one of acrylic acid, methacrylic acid, myristic acid, 11-hexadecenoic acid, 10-undecenoic acid, 11-dodecenoic acid, isokaurenoic acid, 14-pentadecenoic acid, 22-tricosenoic acid, 12-tridecenoic acid, 11-dodecenoic acid, 4-aminohex-5-enoic acid, 9-methoxycarbonyldec-9-enoic acid, 3-butenoic acid, 2,2-dimethyl-3-butenoic acid, 2-methoxybutenoic acid, 2-methyl-3-butenoic acid, 4-pentenoic acid, cyclopentenoic acid, 3-pentenoic acid, 2-methyl-2-pentenoic acid, 4-amino-5-hexenoic acid, 5-hexenoic acid, 4-methyl-3-hexenoic acid, 6-heptenoic acid, 3-heptenoic acid, 2-heptenoic acid, 7-octenoic acid, 3-octenoic acid, 2-octenoic acid, and 8-nonenoic acid. In this embodiment, methacrylic acid is specifically selected.
[0074] The hard monomer is selected from at least one of methyl methacrylate, styrene and acrylonitrile. In this embodiment, methyl methacrylate is specifically selected.
[0075] Optionally, in step S2, The negative pressure is specifically a vacuum process to form an environment below 1 atmosphere. In this embodiment, the vacuum degree is specifically minus 1 atmosphere.
[0076] The dispersant can be selected from one or more of the following brands of reagents provided by German BYK Chemical, specifically BYK-300, BYK-301, BYK-302, BYK-306, BYK-307, BYK-308, BYK-310, BYK-320, BYK-322, BYK-323, BYK-326, BYK-331, BYK-330, BYK-332, BYK-333, BYK-336, BYK-341, BYK-342, BYK-344, BYK-345, BYK-346, BYK-347, BYK-348, BYK-349, BYK-350, BYK-352, BYK-353, BYK-354, BYK-355, BYK-356, BYK-357, BYK-358, BYK-359, BYK-360, BYK-361, BYK-362, BYK-363, BYK-364, BYK-365, BYK-366, BYK-367, BYK-368, BYK-369, BYK-370, BYK-371, BYK-372, BYK-373, BYK-374, BYK-375 YK-353, BYK-354, BYK-355, BYK-356, BYK-357, BYK-359, BYK-370, BYK-371, BYK-373, BYK-375, BYK-377, BYK-378, BYK-385, BYK-381, BYK-390, BYK -394, BYK-399, BYK-392, BYK-110, BYK-190, BYK-W9010, BYK-P104S , BYK-2050, BYK-9076, BYK-163, BYK-168, BYK-170, BYK-192.
[0077] The dispersant can also be selected from one or more of the following brands of reagents provided by Germany's Digo, specifically TEGO-610, TEGO-610S, TEGO-628, TEGO-630, TEGO-650, TEGO-651, TEGO-652, TEGO-653, TEGO-655, TEGO-656, TEGO-660C, TEGO-662C, TEGO-670, TEGO-671, TEGO-685, TEGO-688, TEGO-700, TEGO-710, TEGO-752W, TEGO-240, TEGO-250, TEGO-260, TEGO-265, TEGO-270, TEGO-280, TEGO-500, TEGO-505, TEGO-510.
[0078] The dispersant can also be selected from one or more of the following brands of reagents provided by Hemmings Special Chemicals of Taiwan, China, specifically Levaslip 466, Levaslip 411, Levaslip 876, Levaslip 432, Levaslip875, Levaslip 879, Levaslip 872, Levaslip 435, Levaslip 825, Levaslip 495, Levaslip835, and Levaslip 837.
[0079] In this embodiment, BYK-163 is specifically selected.
[0080] Optionally, in step S3, The viscosity of the prepolymer solution is 20 to 150 s for a 4-cup coating flow time at 25° C. Specifically, it is 20 s in this embodiment.
[0081] The oil-soluble initiator is at least one selected from BPO, AIBN and ABVN. ABVN is specifically selected in this embodiment.
[0082] In one embodiment, in the liquid matrix material, the mass ratio of the prepolymer liquid, the pre-dispersion liquid of the core-shell particles, and the third functional monomer is (60-90): (5-30): (5-10), and the mass ratio of the oil-soluble initiator in the liquid matrix material is ≤0.8%. In this embodiment, the mass ratio of the prepolymer liquid, the pre-dispersion liquid of the core-shell particles, and the third functional monomer (glycidyl methacrylate) is specifically 60:5:5. The mass ratio of the oil-soluble initiator (ABVN) in the liquid matrix material is 0.8%.
[0083] In one embodiment, the process of the polymerization reaction forms a plate with a thickness of less than or equal to 10 mm, specifically a water bath at 35 ~ 65 ° C for 2 ~ 12 h, and a blast air bath at 105 ~ 135 ° C for 1 ~ 8 h. When the thickness exceeds 10 mm, the specific water bath or air bath time should be adaptively extended according to the actual situation. In this embodiment, the thickness is 8 mm, and the polymerization process is specifically a water bath at 45 ° C for 10 h, and a continuous blast air bath at 100 ° C / 2 h, 120 ° C / 3 h, and 135 ° C / 2 h in sequence. Then turn off the heating power supply, naturally cool down to less than 60 ° C, open the oven, and take it out for use.
[0084] Example 2 Compared with Example 1, the difference is In step S1, Optionally, in step S1, The surfactant is specifically selected from sodium dodecyl sulfate.
[0085] The soft monomer is specifically butadiene.
[0086] The crosslinking agent is specifically selected from trimethylolpropane triacrylate.
[0087] The water-soluble initiator is specifically selected from sodium persulfate.
[0088] The first functional monomer is specifically allyl glycidyl ether.
[0089] The second functional monomer is specifically selected from 3-butenoic acid.
[0090] The hard monomer is specifically selected from styrene.
[0091] S11), in this embodiment, the amount of surfactant and deionized water is 0.5 g and 100 g. The amount of soft monomer and crosslinking agent is 10 g and 0.05 g. The amount of water-soluble initiator and deionized water is 0.6 g and 20 g.
[0092] S12), in this embodiment, the amounts of the soft monomer, the surfactant, the cross-linking agent and the first functional monomer are 100 g, 5 g, 5 g and 10 g respectively.
[0093] S13), in this embodiment, the amounts of the hard monomer, the surfactant, the cross-linking agent and the second functional monomer are 100 g, 5 g, 5 g and 10 g respectively.
[0094] Optionally, in step S2, The dispersant specifically selected in this embodiment is TEGO-752W.
[0095] In this embodiment, the mass fractions of the core-shell particles, the dispersant and the MMA monomer are 100, 2 and 10 respectively.
[0096] Optionally, in step S3, The viscosity of the prepolymer solution is specifically 150 s in this embodiment.
[0097] In the liquid matrix material, in this embodiment, the mass ratio of the prepolymer liquid, the pre-dispersion liquid of the core-shell particles, and the third functional monomer (allyl glycidyl ether) is specifically 90:30:10.
[0098] Everything else remains unchanged.
[0099] Example 3 Compared with Example 1, the difference is Optionally, in step S1, The surfactant is specifically selected from sodium dodecyl sulfate.
[0100] The soft monomer is specifically butadiene.
[0101] The cross-linking agent is specifically selected from diallyl terephthalate.
[0102] The water-soluble initiator is specifically ammonium persulfate.
[0103] The first functional monomer is specifically selected from 4-hydroxybutyl acrylate glycidyl ether.
[0104] The second functional monomer is specifically selected from 5-hexenoic acid.
[0105] The hard monomer is specifically selected from acrylonitrile.
[0106] S11), in this embodiment, the amount of surfactant and deionized water is 0.25 g and 100 g. The amount of soft monomer and crosslinking agent is 10 g and 0.025 g. The amount of water-soluble initiator and deionized water is 0.4 g and 20 g.
[0107] S12), in this embodiment, the amounts of the soft monomer, the surfactant, the cross-linking agent and the first functional monomer are 100 g, 2.5 g, 2.5 g and 7 g respectively.
[0108] S13), in this embodiment, the amounts of the hard monomer, the surfactant, the cross-linking agent and the second functional monomer are 100 g, 2.5 g, 2.5 g and 7.5 g respectively.
[0109] Optionally, in step S2, The dispersant is Levaslip 435 in this embodiment.
[0110] Optionally, in step S3, The viscosity of the prepolymer solution is specifically 100 s in this embodiment.
[0111] In the liquid matrix material, in this embodiment, the mass ratio of the prepolymer liquid, the pre-dispersion liquid of the core-shell particles, and the third functional monomer (4-hydroxybutyl acrylate glycidyl ether) is specifically 75:20:12.
[0112] Everything else remains unchanged.
[0113] Control group It is consistent with the existing manufacturing technology of ordinary PMMA materials. It does not involve steps S1 and S2, and directly enters step S3, that is, providing a liquid matrix material, which only includes a prepolymer liquid formed by bulk polymerization of MMA and an oil-soluble initiator. A polymerization reaction is carried out to form a solid matrix from the liquid matrix material. The viscosity of the prepolymer liquid is specifically 100 s in this control group. The mass proportion of the oil-soluble initiator (ABVN) in the liquid matrix material is 0.8%. In this control group, the thickness is 8 mm, and the polymerization process is specifically a water bath at 45 ° C for 10 h, and a continuous blast air bath at 100 ° C / 2 h, 120 ° C / 3 h, and 135 ° C / 2 h in sequence. Then turn off the heating power supply, naturally cool down to less than 60 ° C, open the oven, and take it out for use.
[0114] The performance of the impact-resistant synergistic organic glass manufactured in Examples 1 to 3 and the control group was evaluated as follows. The specific test process is as follows: The shape, size and number of the test specimens used in Examples 1 to 3 and the control group meet the standard requirements of the corresponding tests, and the results are averaged.
[0115] With reference to the requirements and methods in relevant standards such as GB / T 7134-2008 Casting Industrial Organic Glass Sheet, GB / T 40911.3-2021 Plastic Products Polymethyl Methacrylate Sheet Types, Sizes and Characteristics Part 3: Continuous Casting Sheet, and GB / T 2411-2008 Plastics and Hard Rubber Determination of Indentation Hardness (Shore Hardness) Using a Hardness Tester, the basic physical properties were tested and characterized, and the results are shown in Table 1. The results show that compared with the control group, Examples 1 to 3 showed good consistency in tensile strength, tensile elastic modulus, impact strength, tensile fracture strain, bending elastic modulus, hardness, and load deformation temperature, while the bending strength and impact strength were significantly improved. In addition, the present application conducted a stability analysis on the tensile strength, tensile elastic modulus, bending strength, and bending elastic modulus in the data, and the coefficient of dispersion was less than 2%, indicating that the data fluctuated less. Therefore, compared with the ordinary PMMA substrate that has not been treated in any way, the embodiments in the present application have no statistically significant changes in physical and mechanical properties, that is, it is believed that the performance of the two has good consistency.
[0116] Table 1. Basic physical properties statistics
[0117] Note: a The impact strength is the unnotched impact strength of a simply supported beam.
[0118] In Example 3 with the best overall effect, the pre-dispersion liquid of the core-shell particles obtained in step S2) was subjected to transmission electron microscopy ( Figure 5~Figure 7) characterization, the results show that the core-shell colloid particles formed by the technical solution in this application have a nanometer-scale particle size, basically ranging from 50 to 150 nm, which is much smaller than the starting point of the visible light band of 380 nm. The thickness of the shell layer is about 10 nm, and the size consistency is better than the particle size.
[0119] The above control group and Examples 1 to 3 were characterized by UV-Vis spectroscopy in a wavelength range of 200 to 1100 nm. The transmittance test in the visible light region was based on GB / T 7134-2008 Casting Industrial Organic Glass Sheet, and the transmittance data at a wavelength of 420 nm was used. The specific results are shown in Tables 1 and Figure 8 As shown, for Examples 1 to 3, when light enters from the outside and penetrates the matrix, it will encounter the core-shell particles on the path. Since the size of the core-shell particles (less than 200 nm) is much smaller than the starting point of the visible light band (i.e., 380 nm), the visible light wave will be effectively diffracted and pass through almost without loss, thereby basically not affecting the light transmission ability of the visible light band. In addition, the composition structure of the core-shell particles is a cross-linked system (with high heat resistance), and it is chemically bonded to the matrix to form an integral body, so the load heat deformation temperature of the organic glass will be slightly increased.
[0120] The technical solution of this application obtains the preparation process and composition structure of the core-shell colloid particles, as well as the specific functional expression diagram of the impact-resistant synergistic organic glass, see Figure 1 As shown. When the impact-resistant plexiglass encounters strong external stress impact, 1) due to the presence of core-shell particles, the matrix stress diffuses circumferentially along the core-shell particles, dispersing the absorption efficiency of the matrix per unit area for impact strength and increasing the impact toughness of the matrix; 2) the diffusion of matrix cracks is blocked and passivated, and the development of small cracks into destructive through-cracks is stopped in time; 3) the nano-scale core-shell particles show a large specific surface area, that is, the contact area is large enough, and the connection sites or surfaces derived from the elastic deformation of the particles themselves are extremely abundant when subjected to external forces, which can dissipate more impact energy, further increase the failure threshold of the matrix, and protect the structural safety of the material.
[0121] The present application also provides an impact-resistant enhanced organic glass, which is manufactured using the method for manufacturing the impact-resistant enhanced organic glass as described in the above embodiment.
[0122] The above embodiments are merely illustrative of the principles and effects of the present application and are not intended to limit the present application. Anyone familiar with the technology may modify or change the above embodiments without violating the spirit and scope of the present application. Therefore, all equivalent modifications or changes made by a person of ordinary skill in the art without departing from the spirit and technical ideas disclosed in the present application shall still be covered by the claims of the present application.
Claims
1. An impact-resistant synergistic organic glass, characterized in that: The invention comprises a matrix and nano-sized core-shell particles dispersed in the matrix; in a transition region between the core layer and the shell layer of the core-shell particles, a chemical bond is formed between a first functional group contained in the core layer and a second functional group contained in the shell layer; the transition region between the shell layer and the matrix is a compatible interface formed by polymerization and curing of an MMA permeation layer, and in a transition region between the shell layer and the matrix, a chemical bond is formed between the second functional group contained in the shell layer and a third functional group contained in the matrix.
2. A method for manufacturing impact-resistant synergistic organic glass, characterized in that: The following steps are involved: S1, sequentially performing core layer seed formation, core layer growth, shell layer molding and impurity removal and concentration to obtain nano-sized core-shell particles, wherein a first functional monomer containing a first functional group is added during core layer growth; and a second functional monomer containing a second functional group is added during shell layer molding; S2, preparing a pre-dispersion liquid of the core-shell colloid particles, wherein the pre-dispersion liquid comprises the core-shell colloid particles, a dispersant and an MMA monomer; S3, preparing a liquid matrix material, wherein the liquid matrix material comprises a pre-dispersion liquid of the core-shell particles, a pre-polymerization liquid formed by bulk polymerization of MMA, a third functional monomer containing a third functional group, and a thermal initiator; S4, controlling the temperature conditions to polymerize the liquid matrix material to form a solid matrix, and at the same time, forming a chemical bond between the first functional group and the second functional group, and forming a chemical bond between the second functional group and the third functional group, to obtain impact-resistant enhanced organic glass.
3. The method according to claim 2, characterized in that The steps of performing nuclear layer growth include: forming a pre-emulsified solution consisting of a soft monomer, a surfactant, a cross-linking agent and the first functional monomer in a mass ratio of 100: (1 to 5): (1 to 5): (5 to 10); The solution is added dropwise to the core layer seed emulsion at a set rate until the addition is completed to obtain the core layer growth emulsion.
4. The method according to claim 3, characterized in that: The steps of forming the shell layer include: forming a pre-emulsified solution consisting of a hard monomer, a surfactant, a crosslinking agent and the second functional monomer in a mass ratio of 100: (1 to 5): (1 to 5): (5 to 10); The shell layer forming emulsion is obtained by dropping the emulsion into the core layer growth emulsion at a set rate until the dropping is completed.
5. The method according to claim 2, characterized in that The particle size of the core-shell colloid particles is less than 200 nm.
6. The method according to claim 2, characterized in that In S2, the mass ratio of the core-shell colloid particles, the dispersant and the MMA monomer is 100: (0.5 to 2): (5 to 10).
7. The method according to claim 2, characterized in that In the liquid matrix material, the mass ratio of the prepolymer liquid, the pre-dispersion liquid of the core-shell particles and the third functional monomer is (60 ~ 90): (5 ~ 30): (5 ~ 10), and the mass proportion of the thermal initiator in the liquid matrix material is ≤0.8%.
8. The method according to claim 7, characterized in that The viscosity of the prepolymer solution is 20 to 150 s for a 4-cup coating flow time at 25°C.
9. The method according to any one of claims 2 to 8, characterized in that The first functional group and the third functional group are epoxy groups, and the second functional group is a carboxyl group; or the first functional group and the third functional group are hydroxyl groups, and the second functional group is a carboxyl group.
10. An impact-resistant plexiglass, characterized in that: The glass is manufactured by the method for manufacturing the impact-resistant synergistic organic glass as described in any one of claims 1 to 9.
Citation Information
Cited By
Preparation method of impact-resistant wear-resistant PMMA (polymethyl methacrylate) casting plate and PMMA casting plate
CN120923954A